2017
DOI: 10.1038/s41598-017-02667-3
|View full text |Cite
|
Sign up to set email alerts
|

A core extended naphtalene diimide G-quadruplex ligand potently inhibits herpes simplex virus 1 replication

Abstract: G-quadruplexes (G4s) are nucleic acids secondary structures, epigenetic regulators in cells and viruses. In herpes simplex virus 1 (HSV-1)-infected cells, G4s are massively present during viral replication. We here aimed at investigating the possibility to target the HSV-1 G4s by a core extended naphtalene diimide (c-exNDI) G4 ligand. Biophysical and biomolecular analysis proved that c-exNDI stabilized the HSV-1 G4s in a concentration dependent manner. In MS competition assays, c-exNDI preferentially recognize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 41 publications
3
40
0
Order By: Relevance
“…When we measured the infectivity of newly produced progeny virions by infectious center assays, the infectivity of both cell-associated virions and those released into the culture medium was more significantly reduced by treatment of NMM, but not by TMPyP2 ( Fig 7C ). The antiviral effect of G4-stabilizing ligands on herpes simplex virus-1 (HSV-1) has been reported [ 41 , 59 ]. Consistently, we also found that NMM treatment suppresses the growth of HSV-1 ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…When we measured the infectivity of newly produced progeny virions by infectious center assays, the infectivity of both cell-associated virions and those released into the culture medium was more significantly reduced by treatment of NMM, but not by TMPyP2 ( Fig 7C ). The antiviral effect of G4-stabilizing ligands on herpes simplex virus-1 (HSV-1) has been reported [ 41 , 59 ]. Consistently, we also found that NMM treatment suppresses the growth of HSV-1 ( S3 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…We have previously indicated the possible use of G4 ligands as antiviral compounds. Indeed, B19 and other G4 ligands were proven to hinder HSV-1 viral replication without affecting HSV-1 entry (Artusi et al, 2015;Callegaro et al, 2017). Here we further revealed that B19 strongly affects the expression of ICP4 protein acting on its own promoter, thus hampering all subsequent ICP4 transcriptional activities.…”
Section: Discussionmentioning
confidence: 99%
“…To gain further insights into the G4-dependent virus biology, we set out to identify viral/cellular proteins that could specifically interact with biotinylated G4forming HSV-1 sequences. We employed two sequences that have been previously reported to fold into G4s and be highly repeated within the HSV-1 genome: the 58 nt-long un2L2 and 66 nt-long gp054dL3 G4-folding oligonucleotides (Table S1), which are highly conserved and repeated within the terminal and internal repeat short regions (TRS and IRS, RS2) and the UL36 coding sequence (CDS, UL RS1), respectively (Artusi et al, 2015;Callegaro et al, 2017). Un2L2 is composed of 9 G-tracts, ranging from three to nine G bases each, gp054dL3 of ten G-tracts of 4-8 Gs each.…”
Section: Hsv-1 Transcription Factor Icp4 Binds To G4-folded Nucleic Amentioning
confidence: 99%
“…Across different types of microbes, the modulation of transcription by G4s and its cascading effect on specific microbial phenotypes appears to be a common theme ( Figure 5). Inhibition of HSV-1 DNA replication ( Figure 4E) [78,79] HIV-1…”
Section: G4s As Antimicrobial Targetsmentioning
confidence: 99%